The Study of students’ motivation in English writing skill of year 3 at Department of Foreign Languages, Faculty of Languages, Souphanouvong University - BOUNTHAVONG, Oudalon; KEOMANY, Vathsana (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
The objective of this research was to study the types of students’ motivation in English writing skill and the participants of study were third year English students at Faculty of languages, Souphnouvong University, academic year 2017-2018. The sample consisted of 33 students, 26 Males and 7 females who study in year three, Department of Foreign Languages, Majoring in English. They were selected using cluster sampling. This study was quantitative research with instruments is questionnaires to distribute included 20 questions. The data was analyzed by program SPSS for windows quantitative analysis. The collection data lasted 1 week, the mean, percentage and standard deviation were used for data analysis. The finding of this study were as follows: Students’ had motivate in English writing from both types of motivation as intrinsic motivation and extrinsic motivation showed that students had intrinsically motivated more than extrinsically motivated, it shown we seen overall mean intrinsic motivation is 4.21 and extrinsic motivation 3.92. So that, researcher summarized intrinsic motivation was the dominant type study motivation In English writing skills of year three at Department of English, Faculty of Languages, Souphnouvong University.